Synthesis and Performance Evaluation of a New Deoiling Agent for Treatment of Waste Oil-Based Drilling Fluids. (22nd June 2014) - Liu, Pingting; Huang, Zhiyu; Deng, Hao; Wang, Rongsha; Xie, Shuixiang
Abstract : Oil-based drilling fluid is used more and more in the field of oil and gas exploration. However, because of unrecyclable treating agent and hard treatment conditions, the traditional treating technologies of waste oil-based drilling fluid have some defects, such as waste of resource, bulky equipment, complex treatment processes, and low oil recovery rate. In this work, switchable deoiling agent (SDA), as a novel surfactant for treatment of waste oil-based drilling fluid, was synthesized by amine, formic acid, and formaldehyde solution. With this agent, the waste oil-based drilling fluid can be treated without complex process and expensive equipment. Furthermore, the agent used in the treatment can be recycled, which reduces waste of resource and energy. The switch performance, deoiling performance, structural characterization, and mechanisms of action are studied. The experimental results show that the oil content of the recycled oil is higher than 96% and more than 93% oil in waste oil-based drilling fluid can be recycled. The oil content of the solid residues of deoiling is less than 3%.